A systems approach to small group interaction - Tubbs, Stewart L. 1943- (McGraw-Hill, 1995)
Integrates important topics encountered in small group communication into a single comprehensive model. The text's combination of readings, cases and exercises offers the reader the opportunity to view important concepts in practice.